Perceptional differences in the factors of local acceptance of waste incineration plant - Huang, Yangsen; Zhang, Ziqi; Zhang, Yanbo; Wang, Zixing (Frontiers in Psychology, 2022)
Existing research has documented that public attitudes towards waste incineration plants are determined by various factors, such as risk perception, economic impacts, and social trust. However, the diversity in perceptions within communities hosting waste incineration plants is understudied. Adds to existing knowledge, the present paper employed the Q methodology to examine the perceptions of residents living in the vicinity of a waste incineration plant in Xuzhou, China. The results revealed four perspectives on residents’ perceptions towards waste incineration plants: I do not trust them and feel besieged by risks; I trust local governments but I am unfairly treated; I attach this place a lot but I am unfairly treated; I possess knowledge of waste incineration and feel besieged by risks. Our data show that risk perception, trust per-ception, and political efficacy perception are underlying reasons for local acceptance of waste incineration plants. The diversified subjectivities we obtained supplement existing literature that quantitatively documents the influencing factors. These findings demonstrate that it is necessary to explicitly consider the deep-seated values and perspectives among hosting resi-dents’ for the siting of the waste incineration plant.